Analisis kadar total flavonoid pada daun dan biji pepaya (carica papaya l.) Menggunakan metode spektrofotometer Uv-Vis - Putro Panji Asmoro Bangun; Alief Putriana Rahman; Syaifiyatul H (Universitas Islam Madura, 2021)
Analysis of total flavonoid content of papaya leaf and seed extract (Carica papaya L.) by UV-Vis spectrophotometry method. The purpose of this study was because the utilization of papaya leaves and seeds (Carica papaya L.) was still lacking, and to determine the total flavonoid content contained in papaya leaf and seed extract (Carica papaya L.). Extraction of chemical content from the leaves and seeds of papaya (Carica papaya L.) was carried out by maceration method using 96% ethanol. To determine the levels of flavonoid compounds in the sample extract, a compound analysis was performed using UV-Vis spectrophotometry. From the results of the study obtained a qualitative analysis of the flavonoid compounds of each papaya leaf and seed (Carica papaya L.) from 96% ethanol extract changes to brick red color which indicates a positive flavonoid content. Meanwhile, the absorbance measurement was carried out using UV-Vis spectrophotometry with a wavelength of 510 nm. 5 ppm absorbance value (0.214), 10 ppm absorbance value (0.3799), 15 ppm absorbance value (0.5126), and 20 ppm absorbance value (0.7033). As well as measurement of total flavonoid content of papaya leaves (Carica papaya L.) from 96% ethanol extract of 17.4633 mg QE/g or 1.7463% and total flavonoid content of papaya seeds (Carica papaya L.) from 96% ethanol extract of ,8181 mg QE/g or 1,5818%. These results indicate that papaya leaf extract (Carica papaya L.) has higher flavonoid content than papaya seed extract (Carica papaya L.).